MARKETING STRATEGY AT Z&J BAKERY USING SWOT AND QSPM METHODS TO INCREASE SALES VOLUME - Sonnia Kristin; Roni Kastaman; Faizal Syahmurman (Universitas Galuh, 2023)
Since the Covid-19 pandemic has shaken the world and caused economic activity in all countries to be depressed, each country is slowly getting back up. This is evident from the escalating market competitiveness, particularly in a time when technological advancement is moving so quickly. Therefore, it is necessary for every businessperson, like Z&J Bakery, to choose which strategies are appropriate to use. This is because the strategy that has been implemented has not been able to make Z&J Bakery achieve sales targets per month and per year. This research was carried out between November 2021 and July 2022 on Jl. Eyang Weri in Kuningan, West Java, to determine what alternative methods can be implemented and which ones should be prioritized to increase sales volume. The use of IFE, EFE, SWOT quadrant, SWOT analysis, and QSPM matrix were used in this research as a data collection method and to analyze the data obtained.. Results indicate that Z&J Bakery is in the first quadrant, which is in line with the employment of an aggressive strategy. The outcomes of the SWOT matrix are six alternative strategies that could be used. However, the priority strategy to be implemented based on the QSPM matrix is to maintain good relations and expand cooperation with new resellers through providing affordable product prices to further expand the market, because this strategy has the largest STAS score of 4.91.